Complex pattern recognition and evaluation : a knowledge-based approach to computer chess - Ravindra Lal Weeraratne Koggalage (2008)
This thesis describes how existing knowledge of certain positional features of a chess game can be implemented in a parallel evaluation function using the SIMD model. Since SMID machines are very efficient in pattern matching, it is possible to examine thousands of feature patterns associated with chess positions in parallel.